2018
DOI: 10.1371/journal.pone.0193358
|View full text |Cite
|
Sign up to set email alerts
|

Postural sensorimotor training versus sham exercise in physiotherapy of patients with chronic non-specific low back pain: An exploratory randomised controlled trial

Abstract: Sensorimotor training (SMT) is popularly applied as exercise in rehabilitation settings, particularly for musculoskeletal pain. With insufficient evidence on its effect on pain and function, this exploratory randomised controlled trial investigated the potential effects of SMT in rehabilitation of chronic non-specific low back pain. Two arms received 9x30 minutes physiotherapy with added interventions: The experimental arm received 15 minutes of postural SMT while the comparator arm performed 15 minutes of add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 88 publications
2
17
1
Order By: Relevance
“…The achieved results indicated that the explored patients' pain intensity was decreased after conducting 12 weeks of SME; thus, it supports our first hypothesis and is consistent with the study of Ahmed et al [26] and inconsistent with the study of McCaskey et al [29]; this inconsistency may be due to the short duration of the intervention (4 weeks). Pain relief could be related to two mechanisms The firs: the mechanism is due to muscle balance created after SME in the vastus medialis and lateralis muscles.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The achieved results indicated that the explored patients' pain intensity was decreased after conducting 12 weeks of SME; thus, it supports our first hypothesis and is consistent with the study of Ahmed et al [26] and inconsistent with the study of McCaskey et al [29]; this inconsistency may be due to the short duration of the intervention (4 weeks). Pain relief could be related to two mechanisms The firs: the mechanism is due to muscle balance created after SME in the vastus medialis and lateralis muscles.…”
Section: Discussionsupporting
confidence: 84%
“…To improve the proper activation of this group of muscle exercises that aim to automate more complex synergies was used. They included synergies that involved multiple joints, muscles, and motor levels [29].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the blinding of participants in exercise studies is exceedingly difficult because the participants notice if they are exercising or not. To minimize the risk of bias arising from not blinding participants (e.g., due to expectation effects), it is recommended that future studies should control appropriately for confounders, for instance, by assessing additional biopsychosocial variables (e.g., sleep, level of arousal, mood) [114][115][116][117][118] and/or a placebo group [116] (e.g., the placebo [sham] group performs the same exercise but without loading [119,120] or an inadequate dose to induce considerable effects [121]) when possible. Furthermore, with respect to the domain of "other bias", we recommend that upcoming studies pay stronger attention to developing a more rigorous study design (see the next Section 4.2, Study characteristics, for a detailed discussion, as well as Figure 4) [33] and better exercise prescription (see Section 4.3, Exercise characteristics, for a detailed discussion).…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Since these altered adaptative strategies may play a role in the development and maintenance of chronic low back pain, targeted interventions have been developed. Among these, sensory motor training seem promising and although they induce little changes on APA strategies, results indicate a positive impact on pain and function [ 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%